Contesting Identity and Da’wah: The Alawiyyin Debate over Manhaj Kasru Saif in Contemporary Indonesia - Ahmad, Fajar Hidayatulloh; Göktaş, Vahit (Journal of Islamic Philosophy and Contemporary Thought, 2023)
This article examines the internal contestation among Indonesian Alawiyyin (commonly known as habaib) in defining and actualizing manhaj kasru saif—a term signifying approaches to Islamic preaching. The Alawiyyin community has become polarized between two dominant tendencies: one advocating a soft, courteous style of da’wah, and another embracing a confrontational, politicized posture often grounded in claims of genealogical superiority. This divergence is deeply rooted in the historical marginalization of peranakan Hadhrami under colonial segregation, which has shaped contemporary identity discourses. Drawing upon socio-historical analysis and library research, the article explores how differing interpretations of the concept of kafā’ah (social and genealogical parity) contribute to internal tensions regarding religious authority, public engagement, and communal representation. The findings suggest that the debate over manhaj kasru saif reflects a broader struggle over religious identity, political relevance, and the negotiation of inherited authority in postcolonial Indonesia.